STUDI PERBANDINGAN RANTAI PEMASARAN TANDAN BUAH SEGAR KELAPA SAWIT DI DESA JONGGON KABUPATEN KUTAI KARTANEGARA - Ahmad Reza Vahlevi; Ernita Obeth; Budi Winarni (Politeknik Pertanian Negeri Samarinda, 2020)
This research is motivated by oil palm farmers, which is in contrast to the high demand for fresh fruit bunches, as the main raw material for producing crude palm oil. On the other hand, oil palm smallholders are also involved in several different supply chains. The purpose of this study was to determine the management of fresh fruit bunches marketing and the amount of profit received by farmers through the marketing of oil palm fresh fruit bunches in Jonggon Village, Kutai Kartanegara Regency. The analytical method used is descriptive quantitative and marketing margin analysis. The method of determining respondents used purposive sampling method and the respondents in this study were plasma and non-plasma farmers, collector traders and plasma cooperatives, and crude palm oil processing factories owned by PT. Niaga Mas Gemilang in Jonggon Village, Kutai Kartanegara Regency. The results of the respondents' research are in 2 running marketing channels, namely the first marketing channel, namely farmer-cooperative-processing factory, and the second one is farmer-trader-processing factory. Farmers involved in the first supply chain get a profit of Rp. 900 / kg and the farmers involved in the second supply chain get a profit of Rp. 1070 / kg.